2008
DOI: 10.1002/chem.200702029
|View full text |Cite
|
Sign up to set email alerts
|

Designed Peptides with Homochiral and Heterochiral Diproline Templates as Conformational Constraints

Abstract: Diproline segments have been advanced as templates for nucleation of folded structure in designed peptides. The conformational space available to homochiral and heterochiral diproline segments has been probed by crystallographic and NMR studies on model peptides containing L-Pro-L-Pro and D-Pro-L-Pro units. Four distinct classes of model peptides have been investigated: a) isolated D-Pro-L-Pro segments which form type II' beta-turn; b) D-Pro-L-Pro-L-Xxx sequences which form type II'-I (betaII'-I, consecutive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 108 publications
4
55
0
1
Order By: Relevance
“…In solution, the C a 's has an accidental overlap, 28 whereas they are well separated in solids inspite of their larger linewidths ($35 Hz). The most interesting difference is in peptide (1) where doubling of resonance lines are observed in the solid state.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In solution, the C a 's has an accidental overlap, 28 whereas they are well separated in solids inspite of their larger linewidths ($35 Hz). The most interesting difference is in peptide (1) where doubling of resonance lines are observed in the solid state.…”
Section: Resultsmentioning
confidence: 98%
“…Solution state NMR of peptide (1) also showed doubling of resonances. 28 A detailed analysis in solution showed that these doubling was due to the formation of cis and trans isomers across the di-Proline segment in the ratio 3:2, respectively. X-ray study, however, shows the presence of only one cis conformer; therefore, the SSNMR result showing a doubling of resonances is intriguing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations